2021
DOI: 10.1002/dvdy.339
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐beta1 and myeloid‐derived suppressor cells: A cancerous partnership

Abstract: Transforming growth factor-beta1 (TGF-β1) plays a crucial role in tumor progression. It can inhibit early cancer stages but promotes tumor growth and development at the late stages of tumorigenesis. TGF-β1 has a potent immunosuppressive function within the tumor microenvironment that largely contributes to tumor cells' immune escape and reduction in cancer immunotherapy responses. Likewise, myeloid-derived suppressor cells (MDSCs) have been postulated as leading tumor promoters and a hallmark of cancer immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 230 publications
0
8
0
Order By: Relevance
“…In many circumstances, locally produced IL-6 reaches the peripheral circulation and elicits systemic effects such as cachexia and paraneoplastic syndrome, including increased levels of CRP in serum, which was also observed in our HPD patients, resulting in the probable accumulation of MDSCs related to resistance to ICIs. 8 In addition, upregulation of other immune checkpoint suppressor molecules, such as T-cell immunoglobulin mucin-3 (TIM-3) and immunosuppressive MDSCs, can lead to resistance to ICI treatment 12 , 27 and might also promote HPD. These findings indicated that IL-6 might be involved in the immune depressive TiME of HPD.…”
Section: Discussionmentioning
confidence: 99%
“…In many circumstances, locally produced IL-6 reaches the peripheral circulation and elicits systemic effects such as cachexia and paraneoplastic syndrome, including increased levels of CRP in serum, which was also observed in our HPD patients, resulting in the probable accumulation of MDSCs related to resistance to ICIs. 8 In addition, upregulation of other immune checkpoint suppressor molecules, such as T-cell immunoglobulin mucin-3 (TIM-3) and immunosuppressive MDSCs, can lead to resistance to ICI treatment 12 , 27 and might also promote HPD. These findings indicated that IL-6 might be involved in the immune depressive TiME of HPD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that low-dose paclitaxel (10-50 nM) is able to prevent tissue fibrosis by regulating the TGF-β1/Smads signaling pathway and inhibiting the phosphorylation of Smad2/3 to reduce the deposition of collagen [15][16][17] . The results of this study suggest that low-dose paclitaxel inhibits the TGF-β1-induced secretion of collagen in a dose-dependent manner, accompanied by the inhibition on phosphorylation of JNK and Smad2L.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TGF-β1 induces MDSC expansion and immunosuppressive function. Moreover, MDSCs secrete copious amounts of TGF-β, and this cytokine level is elevated in myeloid neoplasm [235,236]; it is plausible that TGF-β1 inhibition may also considerably reduce the number of MDSCs and simultaneously restore the MSC function in the BM niche. Moreover, due to its solid immunosuppressive function, the TGF-β1 block may also promote T-cell function [237].…”
Section: Discussionmentioning
confidence: 99%